Retrospective evaluation of resident pharmacists’ services in a liver intensive care unit: a single-center experience - Meng, Huijie; Ji, Zhaoshuai; Zhang, Zhenyu; Liu, Yuanyuan; Li, Fang; Tang, Jing; Nie, Guangmeng (Frontiers in Pharmacology, 2025)
BackgroundThe engagement of clinical pharmacists in ward-based care remains limited in our hospital. This study explores a novel pharmacist working model (resident pharmacists) and evaluates its effectiveness to provide evidence for optimizing pharmaceutical services in intensive care units (ICUs).MethodsFrom February 2024 to January 2025, resident pharmacists were embedded within the Liver ICU as part of a pilot program, delivering multidisciplinary pharmaceutical services including clinical care, teaching, research, and management. Specialized interventions targeting pediatric and infectious disease populations were implemented based on departmental needs. A retrospective analysis was conducted over 12 months to assess the impact of resident pharmacists on pharmaceutical indicators, service quality, and staff satisfaction; key outcome measures included cost reduction, prescribing appropriateness, and antibiotic use metrics.ResultsAll pharmaceutical management metrics met institutional standards in 2024-2025, including Antibiotic Use Density (AUD; 112.30 vs. threshold 120.47), antimicrobial usage rate (78.68% vs. 88.54%), and proton pump inhibitor prescription rationality (100%). Pharmacists conducted 78 clinical consultations (65.38% multidisciplinary), addressed 132 medication inquiries, developed two clinical guidelines, and achieved full satisfaction scores from medical staff. The average drug cost per patient decreased by 20.05% (RMB 28,806 vs. 36,028 in 2023), with drug cost proportion declining from 30.85% to 23.59%.ConclusionBy deeply participating in various aspects of drug use in the wards, including medical work, management, scientific research cooperation, continuing medical education, resident pharmacists provided more high-quality pharmaceutical services and promote the improvement of pharmaceutical quality control indicators. Resident pharmacists have become important members of the medical team responsible for medication safety and optimizing treatment plans.